Bioactive Films from Willow Bark Extract and Nanocellulose Double Network Hydrogels - Lohtander, Tia; Grande, Rafael; Österberg, Monika; Laaksonen, Päivi; Arola, Suvi (Frontiers in Chemical Engineering, 2021)
In nature, the protection of sensitive components from external threats relies on the combination of physical barriers and bioactive secondary metabolites. Polyphenols and phenols are active molecules that protect organisms from physical and chemical threats such as UV-irradiation and oxidative stress. The utilization of biopolymers and natural bioactive phenolic components as protective coating layers in packaging solutions would enable easier recyclability of materials and greener production process compared to the current plastic-based products. Herein, we produce a fully wood-based double network material with tunable bioactive and optical properties consisting of nanocellulose and willow bark extract. Willow bark extract, embedded in nanocellulose, was cross-linked into a polymeric nanoparticle network using either UV-irradiation or enzymatic means. Based on rheological analysis, atomic force microscopy, antioxidant activity and transmittance measurements, the cross-linking resulted in a double network gel with enhanced rheological properties that could be casted into optically active films with good antioxidant properties and tunable oxygen barrier properties. The purely biobased, sustainably produced, bioactive material described here broadens the utilization perspectives for wood-based biomass especially wood-bark extractives. This material has potential in applications where biodegradability, UV-shielding, and antioxidant properties of hydrogels or thin films are needed, for example in medical, pharmaceutical, food and feed applications, but also as a functional barrier coating in packaging materials as the hydrogel properties are transferred to the casted and dried films.